Effect of altitude of flock location, season of milk production and ripening time on the fatty acid profile of Pecorino Sardo cheese. (February 2021) - Correddu, Fabio; Murgia, Marco A.; Mangia, Nicoletta P.; Lunesu, Mondina F.; Cesarani, Alberto; Deiana, Pietrino; Pulina, Giuseppe; Nudda, Anna
Abstract: The influence of different altitudes of flock location, grazing seasons and ripening time on the fatty acid (FA) profile of Pecorino Sardo cheese was investigated. Milk and thirty-six cheeses, representative of 12 zones (4 provinces × 3 altitudes of flock) and 3 seasons of milk production, were analysed by gas-chromatography for FA profile, at 60 and 120 days of ripening. Data were analysed with a linear model, where altitude, season, ripening time, and their interactions were the fixed factors. Milk FA profile was considered at 0 day of ripening. Altitude did not affect the FA profile, but this was influenced by the seasonality of the botanical composition of grazed pasture, with higher concentration of some interesting FA (i.e., vaccenic, rumenic and α-linolenic acids) in late winter, and lower concentrations occurred in summer-time, possibly caused by under-nutrition during this period. The FA profile was also influenced by the ripening time.